Seventy years of the Journal of Tropical Biology: historical trends by topic, authorship, country, and institution - Nielsen-Muñoz, Vanessa; Azofeifa-Mora, Ana Beatriz; Monge-Nájera, Julián (Revista de Biología Tropical, 2023)
Introduction: The Revista de Biología Tropical is a leading scientific publication in the field of tropical research. For over 70 years, it has adhered to international standards of quality and treated authors with scrupulous fairness. The journal has been recognized for its contribution to biodiversity and ecology research in Latin America. Furthermore, it has been a key vehicle for the dissemination of research related to Costa Rican biology, highlighting Costa Rica as a leader in productivity and scientific impact in the region. Objective: To identify historical trends over the first 70 years of the journal in terms of topics, languages, and the origin of articles. Methods: Using a random number generator, we selected several articles per issue, totaling 704 articles from the Revista de Biología Tropical published between 1953 and 2021. We manually reviewed authorship, languages, countries, topics, and institutions. We categorized article topics by expert criteria, based on a predefined list. Results: There is a trend toward an increase in the number of articles and authors per article, as well as in the use of the English language. The five countries that have published the most in the journal are Costa Rica, Mexico, the United States, Colombia, and Brazil, with the majority of authors affiliated with universities. There is a historical trend toward more collaboration among institutions and countries, with most inter-institutional collaborations between universities, and a clear trend toward increasing international collaboration. Conclusions: In its first 70 years of existence, the Revista de Biología Tropical has published a significant number of contributions to scientific knowledge in tropical biodiversity. It follows global trends of longer and more complex articles with more authors, resulting in growing collaboration among university authors from various institutions and countries, who are increasingly using English as a lingua franca. Costa Rica, Mexico, the United States, Colombia, and Brazil stand out in this regard.